The possibilities to utilise the international experience to map the poverty in Lithuania - Ivaškaitė, Viginta; Lazutka, Romas (Socialinė teorija, empirija, politika ir praktika, 2006)
The possibilities to utilise the international experience of poverty mapping is discussed in the paper. The conceptualisation of poverty map is presented in the first part. The authors present the main groups of poverty indicators, the dimensions of the indicators, methods and factors, the indicators used by international organisations. The exploration of data sufficiency is analysed in the second part. The authors combine the data from household research and census. The results suggest the data sufficiency for the composition of poverty map in Lithuania.
Keywords: Poverty map; Household budget research; Census data; Lithuania